Penguatan Ekonomi Lokal Desa Sendangdawung Melalui Workshop dan Pendampingan UMKM - Indira Aisha; Yasinta Istighfan; Ita Karimatussya’fi; Awang Kurniawan; Muhammad Kholil; Wening Wihartati (Lembaga Pengembangan Kinerja Dosen, 2024)
The Community Service Program (KKN) of UIN Walisongo in Sendang Dawung Village, Kendal Regency, aims to develop the local economy by strengthening Micro, Small, and Medium Enterprises (MSMEs). Intensive discussions with the village community identified various local potentials, such as agricultural products, handicrafts, and traditional processed foods. However, challenges faced include limited capital, restricted market access, and a lack of managerial skills. To address these issues, a series of workshops and mentoring programs were designed, covering business management training, product quality improvement, business digitalization, and ongoing support. Additionally, collaboration with various local stakeholders, such as the Cooperative and MSME Office and financial institutions, was established to enhance support for village MSMEs. The results of this program are expected to increase the competitiveness of MSME products, open up broader market access, and ultimately improve the welfare of the Sendang Dawung Village community